2007
DOI: 10.1016/j.bone.2006.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Lower body negative pressure treadmill exercise as a countermeasure for bed rest-induced bone loss in female identical twins

Abstract: Supine weight-bearing exercise within lower body negative pressure (LBNP) alleviates some of the skeletal deconditioning induced by simulated weightlessness in men. We examined the potential beneficial effect in women. Because dietary acid load affected the degree of bone resorption in men during bed rest, we also investigated this variable in women. Subjects were 7 pairs of female identical twins assigned at random to 2 groups, sedentary bed rest (control) or bed rest with supine treadmill exercise within LBN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 53 publications
4
74
0
1
Order By: Relevance
“…These effects can be seen primarily in the Shackelford et al 2004 study in Figure 51 and impact on any resorption marker; only LBNP with a vertical treadmill was effective at lessening the increase in NTX and deoxypyridinoline (Smith et al 2003). Interestingly, this same protocol was effective for male twins (Smith et al 2003), but was ineffective for female twins (Zwart et al 2007) …”
Section: Bone Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These effects can be seen primarily in the Shackelford et al 2004 study in Figure 51 and impact on any resorption marker; only LBNP with a vertical treadmill was effective at lessening the increase in NTX and deoxypyridinoline (Smith et al 2003). Interestingly, this same protocol was effective for male twins (Smith et al 2003), but was ineffective for female twins (Zwart et al 2007) …”
Section: Bone Resultsmentioning
confidence: 97%
“…Like previously mentioned, study duration is important to note in analyzing the results. The AG study was only 21 days whereas the traditional countermeasure studies were of much longer duration [30 days (Zwart et al 2007) to 117 days (Shackelford et al 2004)]. As a result, no significant BMD results were seen in the AG study and only few were present in the traditional countermeasure studies.…”
Section: Bone Resultsmentioning
confidence: 99%
“…With the advancement of technology, accelerometers have been used to capture sedentary patterns in an objective manner, thus overcoming the drawbacks of self-reporting. Usage of accelerometers allowed significant results in establishing the influence of sedentary behavior on metabolism [15], vascular health [15] and bone mineral content [16]. Moreover, recent studies link sedentary lifestyle and obesity [17], cancer [18] and psychosocial health [19].…”
Section: Sedentary Work Stylementioning
confidence: 99%
“…There is little evidence, however, on whether there is a sex difference in rates of bone loss with unloading or in the rate or magnitude of recovery therefrom. While the effects of bed rest on BMD and/or bone metabolism have been examined separately in men 13,14 and in women, 15,16,17 there have been no human studies that have been statistically powered to make direct sex comparisons. In one 17-week bed rest study that included both men (n = 13) and women (n = 5) at one of 10 sites measured (calcaneus), bone loss was markedly less in women than men.…”
Section: Time Course and Magnitude Of Response: Bonementioning
confidence: 99%
“…6 However, the dual energy x-ray absorptiometry-assessed total hip BMD for women in a 60-day bed rest study 17 revealed a substantial loss at that site, whereas men in a similar study did not have a decrease in total hip bone mineral content. 13 Volumetric BMD and bone geometry of tibial cancellous and cortical compartments have been evaluated after prolonged bed rest using peripheral quantitative computed tomography (pQCT) in men 13,15 and high-resolution pQCT in women. 16 The small gender differences observed in the bone loss rates at those tibial sites are within the reported precision for these pQCT variables.…”
Section: Time Course and Magnitude Of Response: Bonementioning
confidence: 99%